Renewable resource-based composites of recycled natural fibers and maleated polylactide bioplastic: Characterization and biodegradability - Wu, Chin-San (Polymer degradation and stability, 2009)
The thermal properties of composite materials composed of polylactide (PLA) and green coconut fiber (GCF) were evaluated. Blends containing maleic anhydride-grafted PLA (PLA-g-MA/GCF) exhibited noticeably superior thermal properties due to greater compatibility between the two components. The dispersion of GCF in the PLA-g-MA matrix was highly homogeneous as a result of ester formation, and the consequent creation of branched and cross-linked macromolecules, between the carboxyl groups of PLA-g-MA and the hydroxyl groups in GCF. In addition, the PLA-g-MA/GCF blend was more easily processed due to a lower melt viscosity. Each composite was subject to biodegradation tests in a Burkholderia cepacia BCRC 14253 compost. The bacterium completely degraded both the PLA and the PLA-g-MA/GCF composite films. Morphological observations indicated severe disruption of the film structure after 9–12 days of incubation. The PLA-g-MA/GCF (10 wt%) films were not only more biodegradable than those made of PLA, but also exhibited lower molecular weight and intrinsic viscosity, implying a strong connection between these characteristics and biodegradability.